Measuring democratic legitimacy within regional organizations - a member states’ perspective - Zeller, Andrea (Frontiers in Political Science, 2024)
Since the 1990s, the number and international authority of regional organizations (ROs) have increased significantly. Former national decisions are increasingly being taken at the regional level, affecting governance in (democratically constituted) member states. Brexit demonstrated that democratic legitimacy could play a central role for ROs. As states have different (power) resources and political cultures and often do not benefit equally from their membership, democratic legitimacy likely varies between RO member states. This contribution provides a measurement of the democratic legitimacy of a RO's governance in member states in a selected policy field. The newly developed analytical model can be applied to various ROs and is based on input, throughput, and output legitimacy and the empirical acceptance of a RO and its processes. The requirements for democratic legitimacy vary with the authority and intervention of a RO vis-à-vis its member states, and the concept of democracy contained in input legitimacy is oriented towards the normative core of democracy. This analytical approach aims to highlight and compare the democratic legitimacy of various members of a RO in new or established policy fields and contribute to the discussion on why a member state leaves a RO.